Classification of Banks on the Basis of their Capital Adequacy: The Case of Turkey - Boyacioglu, Melek Acar; Avci, Engin (Int Inst Social & Economics Sciences-Iises, 2013)
Banks need to increase their resistance in order to reduce to a minimum the damages that economic crises may do to countries. In this context, the Basel Committee set forth a series of principles aimed at improving efficient risk management and market discipline in banks, increase the efficiency of capital adequacy measurements and in this way ensure financial stability by establishing an effective banking system. One of these principles concerns capital adequacy of banks, which are building blocks of the financial sector. According to this, banks need to have capital adequacy as a precaution against any risks they may be exposed to. The purpose of this study is to determine the banks in the Turkish banking sector that are similar or different in terms of their capital adequacy. In this framework, 45 banks were classified using the fuzzy c-means clustering on the basis of their capital adequacy ratios belonging to the year 2012.
Keywords: Capital Adequacy; Turkish Banks; Fuzzy c-Means Clustering